PENGARUH PEMBELAJARAN MIND MAPPING TERHADAP HASIL BELAJAR SISWA PADA MATERI MEMAHAMI DASAR-DASAR ELEKTRONIKA SEDERHANA - Adi Hardian; Debora; Wiyogo (Steam Engineering, 2019)
The purpose of this study is knowing the mind maping learning strategies against student learning outcomes in understanding simple electronic basics lesson. This research is a type of pre-experimental research with the method of a pretest-posttest design group. Samples from this study were students of class X in motorcycle engineering (TBSM) who numbered 19 people. Research data is quantitative data from learning outcomes test instruments in the form of pretest scores and posttest scores. Instrument test results from 50 multiple choice choices items obtained 30 questions received to be used as instruments in this research. Parametric hypothesis test results obtained price calculate > t table (6,21 > 2,03). Because t = 6,21 is greater than t table = 2,03, so this means H1 is received, what is required about learning strategies mind mapping of student learning outcomes in lesson material understanding simple electronic basics. Results can be investigated student learning outcomes after learning with learning strategies mind mapping is better than student learning outcome before learning with learning strategies mind mapping.